PROFITABILITAS DAN KERAGAAN PERTUMBUHAN BENIH IKAN Tor tambroides DENGAN FREKUENSI PAKAN YANG BERBEDA - Subagja, Jojo; Radona, Deni (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Fish of Tor genus have a slow growth character that resulted in increasing production cost. The high production cost is related to the high price of feed. Fish growth can be triggered by an optimal feeding. A feeding strategy is needed to improve the efficiency of production cost. This study aimed to determine the profitability and the performance of the seedling thai mahseer fish with different feeding frequencies. This study was conducted in Germplasm Research Station, Cijeruk in March-April 2014. The fish used in the experiment have a standard length of 2.29 ± 0.12 cm and weight of 0.32 ± 0.07 g derived from induced breeding spawning of the broodstock natural catches which was adapted for four years in pond concrete. The fish were reared in the aquarium (dimension= 40 x 30 x 30 cm) with a water height of 20 cm and a stocking density of 50 individuals each. The experiment was designed by using three treatments and three replications for each treatment. Fish were feed using commercial feed (protein content = 28%) as much as 20% per day of the total biomass. The treatment observed was feeding frequency, namely (A) three times/day, (B) twice/day, (C) once/day. Results of the experiment for 40 days showed that the increasing values of length, weight, specific growth rate, survival rate, biomass and FCR were not significantly difference (P>0.05). The highest benefit value was obtained in the treatment of feeding with a frequency of three times/day (Rp. 332.304 ± 14.819,-).